Gentrification and its association with health inequalities in Barcelona (2011–2017) - González-Marín, Patricia; Vásquez-Vera, Hugo; López-Gay, Antonio; Peralta, Andrés; Solana-Solana, Miguel; Fernández, Ana (Frontiers in Environmental Health, 2023)
Background. Prior studies have reported conflicting findings on the impact of gentrification of neighborhood residents. While some suggest it could worsen mental health, others indicate improved self-perceived health, although this effect may vary among social groups. This study aimed to determine health inequities, according to socioeconomic position, among residents of different neighborhoods of Barcelona between 2011 and 2017, considering the intensity of the gentrification process.Methods. Observational study with two transversal cuts (2011 and 2017). Neighborhoods were categorized into three groups based on the intensity of gentrification: intensive, moderate-mild, and no gentrification processes. We fitted Poisson robust models to estimate the prevalence ratio (PR) of poor self-reported and poor mental health according to socioeconomic position (social class III vs. I). We then calculated relative differences between 2011 and 2017 through the interaction between the year and socioeconomic position (PRi). The calculations were adjusted for age and household disposable income in the neighborhood and were stratified by sex.Results. In neighborhoods undergoing moderate or mild gentrification during the study period, we found widening inequities in mental health between the most disadvantaged social class and the most privileged social class. Between 2011 and 2017, relative differences in poor mental health increased in moderate-low gentrification neighborhoods [women: PRi: 2.51 (1.52-4.17); men: PRi: 1.99 (1.09-3.61)], equivalent to an increase of 12.9 and 11.5 percentage points, respectively. No statistically significant differences were found in the other neighborhoods.Discussion. The increase in mental health inequalities observed among residents of transitional neighborhoods could be explained by factors such as residential insecurity, eviction from the neighborhood, and rising housing prices.